The effect of temperature and other factors on plastics. (Plastics Design Library, 1990)
This handbook is a source of numeric data on the effect of temperature and on other environmental factors such as humidity on mechanical, electric, and thermal properties of commercial plastics. This handbook presents over 1,700 curves of 53 types for 52 generic families of plastics, including over 330 different grades. The mechanical properties of materials vary depending on the type of stress applied. This handbook also contains mechanical property data for the following stress types: tension, flexure, torsion, impact, and compression. These terms are posted in the filed Load Type. Each material is described in this handbook on three levels. Every material is identified by generic family and often by chemical name. On the hierarchically highest level, all materials are separated into three classes: thermosets, thermoplastics, and thermoplastic elastomers. Data are compiled from various published and limited distribution sources, including commercial catalogs, journal articles, technical reports, materials information sheets, etc. Most of the test data is produced by the material manufacturers.
Chiefly graphs.
Includes index.
Keywords: Plastics -- Effect of temperature on -- Charts, diagrams, etc.; elektronické knihy; electronic books